2004
DOI: 10.1242/jcs.01393
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization established by claudin-11-based tight junctions in stria vascularis is required for hearing through generation of endocochlear potential

Abstract: Claudins are cell adhesion molecules working at tight junctions (TJs) that are directly involved in compartmentalization in multicellular organisms. The cochlea includes a rather peculiar compartment filled with endolymph. This compartment is characterized by high K+ concentration (∼150 mM) and a positive endocochlear potential (∼90 mV; EP), both indispensable conditions for cochlear hair cells to transduce acoustic stimuli to electrical signals. These conditions are thought to be generated by the stria vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 45 publications
6
142
1
Order By: Relevance
“…6H). The absence of expression of the basal cellspecific protein claudin 11 (Cldn11) (Gow et al, 2004;Kitajiri et al, 2004) in Tbx18KO mice (Fig. 6J) confirmed the dramatic reduction of the basal cell layer.…”
Section: Loss Of Basal Cells In the Stria Vascularis Of Tbx18ko Micementioning
confidence: 54%
“…6H). The absence of expression of the basal cellspecific protein claudin 11 (Cldn11) (Gow et al, 2004;Kitajiri et al, 2004) in Tbx18KO mice (Fig. 6J) confirmed the dramatic reduction of the basal cell layer.…”
Section: Loss Of Basal Cells In the Stria Vascularis Of Tbx18ko Micementioning
confidence: 54%
“…In the inner-ear epithelia, tricellulin is concentrated in tTJs (Riazuddin et al 2006), where the fluid-filled compartments of different ionic compositions of the organ of Corti are required for normal hearing (Kitajiri et al 2004). Riazuddin et al (2006) demonstrated the presence of at least four alternatively spliced TRIC isoforms (TRIC-a, TRIC-a1, TRIC-b, TRIC-c) in various mouse tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout mice for claudin-1 and -5 exhibit severe newborn lethal phenotypes because of defective water loss from their skin and defects in their blood-brain barrier, respectively (Morita et al, 1999a;Furuse et al, 2002;Nitta et al, 2003). Knockout mice for claudin-11 and -14 were associated with deafness arising from paracellular barrier-based permselective defects in the inner lymph system (Ben-Yosef et al, 2003; Kitajiri et al, 2004;Wattenhofer et al, 2005). It is noteworthy that deficiency of claudin-11 and -19 lead to defects in TJ formation and defective electrical sealing of glial myelin sheath cells in the central and peripheral nervous systems, respectively (Gow et al, 1999;Morita et al, 1999b;Miyamoto et al, 2005).…”
Section: Tj-based Epithelial Microenvironment and Cell Proliferation mentioning
confidence: 99%